Jane Austen, sex, and romance : engaging with desire in the novels and beyond - Nachumi, Nora; Oppenheim, Stephanie (Stephanie M.) (University of Rochester Press, 2022)
"Jane Austen, Sex, and Romance: Engaging with Desire in the Novels and Beyond brings together a range of voices--from literary scholars to video game designers--to explore how different types of readers experience the realm of desire and the erotic in all things Austen. In this timely collection, writers, critics, journalists, and authors of internet content weigh in on sex and romance in Austen's works and in the conversations and creations the novels inspire--from sequels to critical analyses to online role-playing games. Contributors examine what is at stake for each set of Austen enthusiasts when Eros is added to the equation, in so doing building on the long tradition of Austen criticism and enriching our appreciation of the novels"--